2019
DOI: 10.1111/ejh.13267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of unexplained erythrocytosis in Indian patients

Abstract: Objective To evaluate the spectrum of genetic defects in Indian patients with unexplained erythrocytosis. Methods Fifteen families (18 patients) with unexplained erythrocytosis were enrolled after excluding polycythemia vera and secondary erythrocytosis. Focused Sanger sequencing from genomic DNA was performed for EPOR (exon 8), VHL (exons 2‐3), EGLN1 (exons 2‐5), EPAS1 (exon 12), and all exons of HBB, HBA1, and HBA2 genes. Results Eleven of the 18 patients (including two pairs of brothers) had Chuvash polycyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Two other high oxygen affinity variants having substitution in the same position are also described in the literature, namely Hb Barcelona [β 94(FG1)Asp→His] and Hb Bunbury [β 94(FG1)Asp→Asn] 20 . In our study of 18 North Indian CE patients, 3 had high oxygen affinity hemoglobins—1 having a heterozygous Hb McKees Rocks HBB :c.438T>A (p.Tyr146*), and 2 brothers having Hb Rainier HBB :c.437A>G (p.Tyr146Cys) 21 …”
Section: Secondary Congenital Erythrocytosissupporting
confidence: 55%
See 1 more Smart Citation
“…Two other high oxygen affinity variants having substitution in the same position are also described in the literature, namely Hb Barcelona [β 94(FG1)Asp→His] and Hb Bunbury [β 94(FG1)Asp→Asn] 20 . In our study of 18 North Indian CE patients, 3 had high oxygen affinity hemoglobins—1 having a heterozygous Hb McKees Rocks HBB :c.438T>A (p.Tyr146*), and 2 brothers having Hb Rainier HBB :c.437A>G (p.Tyr146Cys) 21 …”
Section: Secondary Congenital Erythrocytosissupporting
confidence: 55%
“…We recently reported 18 patients from 15 North Indian families presenting with unexplained erythrocytosis using focused Sanger sequencing. Eleven patients from nine families were homozygous for VHL :c.598C>T (p.Arg200Trp), making it a recurrent genetic abnormality in the north Indian population 21 …”
Section: Secondary Congenital Erythrocytosismentioning
confidence: 99%
“…Genetic mutations in the erythropoiesis and hypoxia sensing pathways have been detected in upto 20% patients of IE [21]. Studies, including one from India suggest that patients with EPO level below normal may be screened for mutations involving the EPO signalling pathway (EPOR exon 7-8) while those with an inappropriately normal EPO level with respect to their Hb may be screened for mutations in the oxygen sensing pathway (VHL, PHD2, HIF2a, b globin and a globin gene) [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical laboratories that lack facilities for oxygen-saturation curve analysis may calculate the p50 mathematically using venous blood gas analysis parameters 3. Genetic confirmation is often also straightforward using direct DNA sequencing of the relatively small globin genes by Sanger’s method 1 4 5…”
mentioning
confidence: 99%
“…High oxygen-affinity Hb’s are uncommon causes of congenital erythrocytosis 1 4–6. A prior Indian study found that 3 out of 18 patients with congenital erythrocytosis (including two brothers) had high oxygen affinity variants—Hb McKees Rocks and Hb Rainier 4.…”
mentioning
confidence: 99%